Writing grant proposals that win - Ward, Deborah , 1957- (Jones & Bartlett Learning, 2012)
Writing Grant Proposals That Win offers step-by-step instructions and clear examples of how to write winning grant proposals. It offers practical guidance on how to: express the need for the project; describe objectives and activities; outline an evaluation plan; and create a workable project budget